(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
Open dumpsites are becoming a major global concern in developing countries, causing heavy metal pollution, and posing a serious threat to human and plant health. This study assessed the zinc (Zn) concentration in the roots, stems, and leaves of maize plants growing on various dumpsite soils in Anyigba (Redeem, Market, and Anokwu). The plant tissues were tested for Zn using an Atomic Absorption Spectrophotometer (AAS). The study found that plants grown on a dumpsite had considerably higher Zn concentrations in their roots, stems, and leaves compared to the control site (p<0.05). The concentration of zinc ranges in the following sequence: Control (0.23 mg/kg)>Anokwu (0.62 mg/kg)>Market (0.63 mg/kg)>Redeem (0.80 mg/kg) for Stem; Control (0.34 mg/kg)>Market (0.68 mg/kg)>Anokwu (0.82 mg/kg)>Redeem (1.08 mg/kg) for Leaf; Control (0.66 mg/kg)>Anokwu (0.68 mg/kg)>Market (0.98)>Redeem (1.00 mg/kg). Zinc’s bioconcentration factor (BCF) decreased in the following sequence among dumpsites: Anokwu (0.32 mg/kg) > Market (0.25 mg/kg) > Control (0.18 mg/kg) > Redeem (0.14 mg/kg), all of which exceeded WHO permitted levels. Bioaccumulation concentration (BAC) values range between 0.39 and 0.78 mg/kg, suggesting that maize plant is an excluder, while translocation factor (TF) values were all above 1, indicating that the plants translocate heavy metals from roots to shoots. Our study highlights the critical need for monitoring heavy metal contamination in food crops, especially in regions with open dumpsites, to protect public health. Given the potential risks of zinc bioaccumulation, effective measures are required to mitigate exposure, including soil remediation and the use of cleaner, safer agricultural practices. This research contributes to understanding the environmental and health implications of zinc pollution, emphasizing the urgency of addressing the risks associated with open dumpsites.